PEMANFAATAN GESERAN POLA SPEKTRUM UV SENYAWA GOLONGAN BARBITURAT DALAM UJI KONFIRMASI DENGAN METODE TLC-SPEKTROFOTODENSITOMETRI - Subadra, I Nyoman; Kusuma Dewi, Luh Putu Mirah Kusuma Dewi; Widjaja, I.N.K. Widjaja (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2019)
A Research of the utilization of spectrum shift in confirmation test for barbiturate using TLC-Spectrophotodensitometry has been done. Analyte was analyzed using two mobile phases, that are TD (chloroform: acetone = 80 : 20) and TE (ethyl acetate: methanol: ammonia = 85 : 15 : 5) with Al-TLC Silica 60 GF 254 plate as the stationary phase. Afterwards, plate was sprayed with HCl or KOH. The analyzed parameters were hR f c , normal UV-spectrum pattern and its shift. The correlation of spectrum or the shift of UV-spectrum for barbiturate compounds was determined with Wincats program. The analysis of barbiturates which based on hR f c in error window (±7) for TD system and in error window (±11) for TE, still produced hit factor 8-25 compounds. The confirmation test for barbiturates based on hR f c and r ? 0,95, produced hit factor 1-2 compounds. Barbiturate compounds showed spectrum shift in alkali solution, while in acid solution did not happen. However, all four analytes contained identical spectrum shift, therefore the data of these spectrum shift can not be utilized for confirmation test of barbiturate compounds.